FROM USM TO ANTARCTICA, FOR THE PRESERVATION OF BIODIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 17 February 2016 – There was a deep feeling of gratefulness and excitement shared by the researchers upon arriving on Malaysian soil, on the evening of Sunday, 14 January 2016.